EFEKTIVITAS PENGGUNAAN E-FILING DALAM PELAPORAN SPT YANG TERDAFTAR SEBAGAI WAJIB PAJAK ORANG PRIBADI KARYAWAN - Saraswati M, Ines; Hayatie, Marliza Noor (Bilancia : Jurnal Ilmiah Akuntansi, 2022)
ABSTRACT This study uses the effectiveness ratio used to calculate the E-filing usage level for individual taxpayers registered in the Pelaihari area. The use of this effectivity ratio is by dividing the number of individual taxpayers of employees reporting E-filing by the number of individual employee taxpayer data multiplied by 100%. This study aims to determine the effectiveness of E-filing usage in reporting the SPT of individual taxpayers of employees registered in KP2KP Pelaihari and the understanding level of individual taxpayers registered in KP2KP Pelaihari on E-filing usage. Based on the calculation using the effectiveness ratio, the level of effectiveness on E-filing usage on the individual taxpayers of employees who are registered in KP2KP Pelaihari can be said as quite effective according to the results of the data obtained, but it's just that taxpayer understanding level is lacking on E-filing usage because they do not understand how to fill in the SPT using the E-filing system. Keywords: Efectiveness; e-filing; SPT ABSTRAK Penelitian ini menggunakan rasio efektivitas yang digunakan untuk menghitung tingkat penggunaan E-filing wajib pajak orang pribadi karyawan yang terdaftar di daerah Pelaihari. Penggunaan rasio efektivitas ini yaitu dimana jumlah wajib pajak orang pribadi karyawan lapor E-filing dibagi banyaknya data wajib pajak orang pribadi karyawan dikali dengan 100%. Penelitian ini bertujuan untuk mengetahui efektivitas penggunaan E-filing dalam pelaporan SPT wajib pajak orang pribadi karyawan yang terdaftar diKP2KP Pelaihari serta tingkat pemahaman wajib pajak orang pribadi karyawan yang terdaftar diKP2KP Pelaihari terhadap penggunaan E-filing. Berdasarkan perhitungan menggunakan rasio efektivitas, tingkat efektivitas penggunaan E-filing pada wajib pajak orang pribadi karyawan yang terdaftar diKP2KP Pelaihari sudah bisa dikatakan cukup efektif sesuai dengan hasil data yang diperoleh, namun hanya saja tingkat pemahaman wajib pajak yang kurang terhadap penggunaan E-filing karena belum memahami cara pengisian SPT menggunakan sistem E-filing. Kata Kunci: efektivitas; e-Filing; SPT